Forms of Illocutionary Speech Acts on Deddy Corbuzier’s Podcast - Rettob, Fifi; Pesiwarissa, Leonora Farilyn; Lelapary, Heppy Leunard (Universitas Pattimura, 2024)
This research aims to describe the form of illocutionary speech acts in the Deddy Corbuzier Podcast. The problem studied is the form of illocutionary speech acts in the Deddy Corbuzier Podcast. This type of research is descriptive qualitative. The data in this research are the words of Deddy Corbuzier's Podcast in the episode